2013
DOI: 10.1097/fjc.0b013e318294a1cf
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyclic Guanylate Cyclase Stimulation on Right Ventricular Hypertrophy and Failure Alone and in Combination With Phosphodiesterase-5 Inhibition

Abstract: Stimulation of soluble guanylate cyclase by BAY 41-2272 alone or in combination with sildenafil failed to prevent the development of RV hypertrophy and failure in rats subjected to pulmonary trunk banding. An increased mortality was observed in animals treated by BAY 41-2272 alone and in combination with sildenafil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…19 We observed TR in most of the PTB rats banded with a 0.6-mm clip and in all of the PTB rats banded with a 0.5-mm clip. Tricuspid regurgitation is a significant pathologic factor in PAH and an independent risk factor of transplantation or death in PAH patients.…”
Section: Effects Of Pulmonary Trunk Bandingmentioning
confidence: 54%
See 1 more Smart Citation
“…19 We observed TR in most of the PTB rats banded with a 0.6-mm clip and in all of the PTB rats banded with a 0.5-mm clip. Tricuspid regurgitation is a significant pathologic factor in PAH and an independent risk factor of transplantation or death in PAH patients.…”
Section: Effects Of Pulmonary Trunk Bandingmentioning
confidence: 54%
“…19 Rats were sedated, intubated, and mechanically ventilated with sevoflurane (Abbot Scandinavia, Solona, Sweden; induction: 7.0% in 2:1 O 2 /N 2 O mix; maintenance: 3.5% in 2:1 O 2 /N 2 O mix) at 75 breaths/min and a tidal volume of 10 mL/kg. A lateral thoracotomy was performed and the pulmonary trunk and the aorta carefully separated, enabling the appliance of a titanium clip with an inner diameter of 0.5 mm or 0.6 mm around the pulmonary trunk.…”
Section: Pulmonary Trunk Bandingmentioning
confidence: 99%
“…Sodium nitrite therapy also improves the outcome in monocrotaline-induced pulmonary hypertension in the rat via sGC activation after conversion of nitrite to vasoactive NO [40]. On the other hand, stimulation of sGC by the riociguat-related stimulator BAY 41-2272, with or without inhibition of cGMP phosphodiesterase by sildenafil administration, fails to prevent right ventricle hypertrophy after pulmonary trunk banding in rats [41]. A likely explanation for the discrepancy between these studies is that the surgical procedure performed in the latter study directly induces right ventricular hypertrophy, while the other studies rely on models of primary pulmonary vascular dysfunction.…”
Section: Sgc In the Lung And Its Role In The Pulmonary Vasculaturementioning
confidence: 99%
“…It is an important topic and by using magnetic resonance imaging (MRI) to characterize right ventricular (RV) performance it adds to previous studies on the same subject [26]. The authors conclude that both sildenafil and riociguat prevent RV failure in mice subjected to pulmonary artery banding (PAB) based on improvement in stroke volume (SV) and ejection fraction (EF).…”
mentioning
confidence: 99%
“…Another comment is that previous studies with a similar design in a rat PAB model [6] found that mortality was increased with the soluble guanylate cyclase (sGC) stimulator BAY 41-2272 (a compound similar to riociguat). It should be reported in the paper by Rai and colleagues whether there was any mortality in the treatment arms in this study, as this could potentially introduce a selection bias.…”
mentioning
confidence: 99%